Desempenho e Composição Corporal de Novilhas Alimentadas com Dois Níveis de Concentrado e Bagaço de Cana Submetidos a Diferentes Processos de Hidrólise - Lanna, Dante Pazzanese D.; Morais, Jozivaldo P. [UNESP]; Boin, Celso; Fox, Danny G.; Leme, Paulo Roberto; De Castro, Fernando Basile (My University, 1999)
The objective of this work was to test two forms of hydrolysis of sugarcane bagasse (with [17 kgf/cm 2] or without [4 kgf/cm 2] fast decompression post-hydrolysis) and two levels of concentrate (25 and 45%. DM) on the performance and final body composition of growing heifers in a 112 day feedlot period. Twenty-four Nellore and 12 Canchim heifers were allotted to a randomized block design in a 2x2 factorial arrangement. The results demonstrated that the omission of decompression post hydrolysis and the use of higher levels of concentrate increased daily gain and feed intake. The results for weight gain and dry matter intake, for treatment without vs with decompression and with 45 vs 25% of concentrate, were, respectively, .76 vs .67 and .76 vs .66 kg/d and 6.7 vs 5.8 and 6.8 vs 5.7 kg/d. However, there was no difference among treatments for feed:gain ratio. No differences were observed among treatments for body composition determined by deuterium dilution at the end of the feedlot period, although the estimated rate of lipid deposition was higher for the treatment without fast decompression (216 vs 175 g/d) and the treatment with 45% concentrate (225 vs 166 g/d). No advantage was observed in the fast decompression post-hydrolysis at high pressure on the efficiency of feed:gain ratio of the feeds. The results demonstrated that animals fed hydrolyzed bagasse at high levels of intake (2.9% LW) and lower proportions of concentrate presented an efficiency of feed utilization similar to the diets with higher levels of concentrate.
Performance and Body Composition of Heifers Fed Two Concentrate Levels and Sugarcane Bagasse Submitted to Different Hydrolysis Processes
Keywords: Acid hydrolysis; Body composition; Feedlot; Sugarcane bagasse; Zebu